Development of an Indirect Stereolithography Technology for Scaffold Fabrication with a Wide Range of Biomaterial Selectivity - Kang, Hyun-Wook (Mary Ann Liebert, Inc., 2012)
Tissue engineering, which is the study of generating biological substitutes to restore or replace tissues or organs, has the potential to meet current needs for organ transplantation and medical interventions. Various approaches have been attempted to apply three-dimensional (3D) solid freeform fabrication technologies to tissue engineering for scaffold fabrication. Among these, the stereolithography (SL) technology not only has the highest resolution, but also offers quick fabrication. However, a lack of suitable biomaterials is a barrier to applying the SL technology to tissue engineering. In this study, an indirect SL method that combines the SL technology and a sacrificial molding process was developed to address this challenge. A sacrificial mold with an inverse porous shape was fabricated from an alkali-soluble photopolymer by the SL technology. A sacrificial molding process was then developed for scaffold construction using a variety of biomaterials. The results indicated a wide range of biomaterial selectivity and a high resolution. Achievable minimum pore and strut sizes were as large as 50 and 65 μm, respectively. This technology can also be used to fabricate three-dimensional organ shapes, and combined with traditional fabrication methods to construct a new type of scaffold with a dual-pore size. Cytotoxicity tests, as well as nuclear magnetic resonance and gel permeation chromatography analyses, showed that this technology has great potential for tissue engineering applications.